Epitope-specific antibody-induced cleavage of angiotensin-converting enzyme from the cell surface. - Balyasnikova, Irina V (2002)
Angiotensin I-converting enzyme (ACE; CD143, EC 3.4.15.1) is a type-1 integral membrane protein that can also be released into extracellular fluids (such as plasma, and seminal and cerebrospinal fluids) as a soluble enzyme following cleavage mediated by an unidentified protease(s), referred to as ACE secretase, in a process known as "shedding". The effects of monoclonal antibodies (mAbs) to eight different epitopes on the N-terminal domain of ACE on shedding was investigated using Chinese hamster ovary cells (CHO cells) expressing an ACE transgene and using human umbilical vein endothelial cells. Antibody-induced shedding of ACE was strongly epitope-specific: most of the antibodies increased the shedding by 20-40%, mAbs 9B9 and 3A5 increased the shedding by 270 and 410% respectively, whereas binding of mAb 3G8 decreased ACE shedding by 36%. The ACE released following mAb treatment lacked a hydrophobic transmembrane domain anchor. The antibody-induced shedding was completely inhibited at 4 degrees C and by zinc chelation using 1,10-phenanthroline, suggesting involvement of a metalloprotease in this process. A hydroxamate-based metalloprotease inhibitor (batimastat, BB-94) was 15 times more efficacious in inhibiting mAb-induced ACE shedding than basal (constitutive) ACE release. Treatment of CHO-ACE cells with BB-94 more effectively prevented elevation in antibody-dependent (but not basal) ACE release induced by 3,4-dichloroisocoumarin and iodoacetamide. These data suggest that different secretases might be responsible for ACE release under basal compared with antibody-induced shedding. Further experiments with more than 40 protease inhibitors suggest that calpains, furin and the proteasome may participate in this process.